2016
DOI: 10.1021/acs.biochem.6b00294
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Minimal Peptide Tag for in Vivo and in Vitro Loading of Encapsulin

Abstract: The encapsulation of enzymes and other proteins within a proteinaceous shell has been observed in many bacteria and archaea, but the function and utility of many such compartments are enigmatic. Efforts to study these functions have been complicated by the size and complexity of traditional protein compartments. One potential system for investigating the effect of compartmentalization is encapsulin, a large and newly discovered class of protein shells that are typically composed of two proteins: a protomer tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
160
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(167 citation statements)
references
References 27 publications
5
160
0
2
Order By: Relevance
“…This motif is well-conserved, and the addition of this sequence to heterologous proteins is sufficient to direct them to the interior of encapsulins (Rurup et al, 2014; 2015; Cassidy-Amstutz et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…This motif is well-conserved, and the addition of this sequence to heterologous proteins is sufficient to direct them to the interior of encapsulins (Rurup et al, 2014; 2015; Cassidy-Amstutz et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…A large variety of native cargo proteins has been identified in bacteria and archaea, including peroxidases and ferritin-like proteins involved in stress response pathways 11,[14][15][16] . Using Escherichia coli as a host, it has been shown that packaging of non-native proteins into the encapsulins from Thermotoga maritima and Brevibacterium linens can be achieved by fusion of targeting peptides to the intended cargo 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…All HB‐Enc fusions were transformed and expressed in E. coli C43(DE3) cells from a P T7 promoter; this system was previously found to express highly soluble encapsulin cages (Cassidy‐Amstutz et al, ). All N‐terminal HB‐Enc constructs showed overexpression of soluble HB‐Enc protein by SDS‐PAGE and anti‐His 6 Western blot (Figure a).…”
Section: Resultsmentioning
confidence: 99%